2017
DOI: 10.1016/j.apmr.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Self-Efficacy and Secondary Health Conditions in People Living With Spinal Cord Injury: A Systematic Review and Meta-Analysis

Abstract: Self-efficacy is negatively associated with depressive and anxiety symptoms in SCI. Therefore, self-efficacy seems an important target in the rehabilitation of patients living with SCI. More research is necessary to clarify the associations between self-efficacy and somatic SHCs. Future research should also focus on different types of self-efficacy and their association with SHCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 64 publications
1
38
0
2
Order By: Relevance
“…Furthermore, one longitudinal study indicated that transitioning from ambulation to wheelchair use can negatively impact psychosocial health 10 years after SCI [37]. One recent meta-analysis study showed that higher self-efficacy had a strong negative correlation with fewer depressive (18 studies) and anxiety symptoms (7 studies), and showed a trend towards a positive correlation between self-efficacy and quality of life [38]. Therefore, self-efficacy seems an important target in the rehabilitation of patients living with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one longitudinal study indicated that transitioning from ambulation to wheelchair use can negatively impact psychosocial health 10 years after SCI [37]. One recent meta-analysis study showed that higher self-efficacy had a strong negative correlation with fewer depressive (18 studies) and anxiety symptoms (7 studies), and showed a trend towards a positive correlation between self-efficacy and quality of life [38]. Therefore, self-efficacy seems an important target in the rehabilitation of patients living with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as a person's ability to organize and implement necessary actions in the face of the situation (12). Having high self-efficacy in patients with SCI-related other chronic diseases can improve well-being, mental health, and health behavior (13)(14)(15). Self-efficacy reduces anxiety and depression symptoms in patients with SCI and is one of the main goals of rehabilitation programs (14).…”
Section: Introductionmentioning
confidence: 99%
“…Having high self-efficacy in patients with SCI-related other chronic diseases can improve well-being, mental health, and health behavior (13)(14)(15). Self-efficacy reduces anxiety and depression symptoms in patients with SCI and is one of the main goals of rehabilitation programs (14). It is an important psychosocial construct that may affect health behavior to control diseases and may also function as a link between effective health promotions and educational interventions and health behavior change in disease control (15).…”
Section: Introductionmentioning
confidence: 99%
“…Another concept associated with high prevalence of SHCs, especially psychological SHCs, is self-efficacy [ 23 ]. Self-efficacy is defined as the belief that one can successfully execute the behavior required to produce the desired outcomes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Negative associations are found between self-efficacy and depression and anxiety. The negative association between self-efficacy and the occurrence of physical SHCs of people with SCI is still unclear [ 23 ]. There is, to date, also limited information about the course of self-efficacy and self-management during and after the SCI rehabilitation.…”
Section: Introductionmentioning
confidence: 99%